Lymphopenia in COVID-19: γδ T Cells-Based Therapeutic Opportunities - Elena Lo Presti; Francesco Dieli; Serena Meraviglia (Vaccines, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection dysregulates the immune system by lymphopenia of B cells, monocytes, eosinophils, basophils, and cytotoxic cells such as CD8, γδ T cells, and natural killer (NK) cells. Despite many studies being conducted to better understand the effects of SARS-CoV-2 on the immune system, many mechanisms still remain unclear, hindering the development of novel therapeutic approaches and strategies to improve the host’s immune defense. This mini-review summarizes the findings on the role of γδ T cells in coronavirus disease 2019 (COVID-19), providing an overview of the excellent anti-viral therapeutic potential of γδ T cells, that had not yet been exploited in depth.